Impacts of the Capillary Blood Glucose Self-monitoring Program on the Quality of Life of Diabetic Patients (Research, Society and Development, 2022)
Introduction: Diabetes Mellitus (DM) is defined as a metabolic disorder that increases blood glucose levels, this is due to its characteristic of not secreting insulin or not producing it, causing hyperglycemia in individuals. Objective: To understand the impacts that the glycemic self-monitoring program generates on the quality of life of diabetic patients. Materials and Methods: This is a descriptive, exploratory, quantitative and qualitative research carried out in two Public Pharmacies in a municipality in the interior of Bahia, from July to October 2022. 52 users registered in the Health Care Program participated in the research. Capillary blood glucose self-monitoring. The instruments for data collection were a questionnaire from the WHOQOL-bref instrument. For the analysis and interpretation of the research data, the descriptive analysis method was used. Results: 37.8% of the patients who consider their quality of life good, however, the casual blood glucose data of some represent blood glucose values ​​between 89 mg/dL to 532 mg/dL, in which they significantly interfere in the patient's life. Conclusion: It is concluded that even the patients with chronic disease and some of them were not able to control the comorbidity, the reference values ​​found in the WHOQOL-bref were between 3.5 and 4.1, which means the quality of the physical domains, psychological, social and environmental conditions were between fair and good.